Ikhtikar, Islamic Business Ethics, Price floor, Price ceiling, role of government. - Maghfuroh, Nuril Laila; Djalaluddin, Ahmad; Asnawi, Nur; Yazid, Azy Athoillah; Muhammad, Zaydan (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2024)
Ikhtikar is a very immoral business strategy, because it can result in injustice, trouble and misery for other business people. In Islamic business ethics, ethical behavior is strictly prohibited because it will inevitably result in a party experiencing losses which will result in injustice in business. This research uses a qualitative method with a descriptive approach to opinions from journals, articles and books about ikhtikar.The results of this research are that endeavor in the view of Islamic business ethics does not really reflect a sharia-compliant businessman because of the greed of the perpetrator of the endeavor to gain large and abundant profits even though he has to sacrifice other business partners. This requires a sharia business spirit and government intervention in dealing with ethical problems by implementing monetary policy and fiscal policy, such as setting a price floor (the most expensive retail price) and a price ceiling (the lowest purchasing price). The price floor is used when there is a shortage of goods on the market, while the price ceiling is applied when the harvest or goods on the market are abundant.